Hubungan Kadar Hemoglobin dan Kadar Kreatinin Darah pada Pasien Gagal Ginjal Kronik Pasca Transfusi Berulang - Eko Naning Sofyanita; Roni Afriansya; Nur Indah Palupi (Poltekkes Kemenkes Semarang, 2020)
Kidneys are part of the body that has an important role. One of the functions of the kidney is the production of erythropoietin. Erythropoietin stimulates the production of red blood cells. People or patients who have kidney problems can cause anemia. This study aims to determine the relationship between hemoglobin levels and blood creatinine levels in patients with chronic kidney disease after receiving a transfusion. Blood creatinine levels in this study were used as an index to measure kidney function. The study was conducted at the Wira Tamtama Hospital Semarang by taking data on 20 patients in 2020 with chronic kidney disease and taking data on hemoglobin (cut-off 12 g/dL) and serum creatinine (cut-off 1.5 mg/dL). The relationship between the two was calculated by chi-square test and found 80% of patients with low hemoglobin in patients with high creatinine levels and 0% of patients with low hemoglobin in patients with normal creatinine levels (p=0.040). There is a risk of decreased hemoglobin levels (OR = 3,442) in patients with high creatinine levels. It was concluded that there was a significant relationship between hemoglobin levels and blood creatinine levels and patients with high creatinine levels tended to be at risk of anemia.